Education for the Next Frontier in Patient Safety: A Longitudinal Resident Curriculum on Diagnostic Error. (November 2017) - Ruedinger, Emily; Olson, Maren; Yee, Justin; Borman-Shoap, Emily; Olson, Andrew P. J.
Diagnostic error is a common, serious problem that has received increased attention recently for its impact on both patients and providers. Presently, most graduate medical education programs do not formally address this topic. The authors developed and evaluated a longitudinal, multimodule resident curriculum about diagnostic error and medical decision making. Key components of the curriculum include demystifying the medical decision-making process, building skills in critical thinking, and providing strategies for diagnostic error mitigation. Special attention was paid to avoiding the second victim effect and to fostering a culture that supports constructive, productive feedback when an error does occur. The curriculum was rated by residents as helpful (96%), and residents were more likely to be aware of strategies to reduce cognitive error (27% pre vs 75% post, P < .0001) following its implementation. This article describes the development, implementation, and effectiveness of this curriculum and explores generalizability of the curriculum to other programs.